101 Independent replication and validation of nanopore-based long read sequencing and methylome classification for rapid brain tumour diagnosis - Vassili Crispi; Luke Ames; Joanne Stockton; Sana Manan; Nicola Chadderton; Lisa James; Sahar Sanai; Tracy Bright; Rajwinder Rai; Santosh Nagaraju; Ute Pohl; Philipe Taniere; et al. (Neuro-Oncology, 2026)
Abstract Introduction Integrated histopathological-molecular analysis is essential to diagnose and guide precision therapies in brain tumours. Whilst standard of care (SoC) diagnostics takes weeks, long read sequencing (LRS) on Oxford Nanopore Technology (ONT) platform and bioinformatics research tools provide rapid diagnosis within hours/days. We independently replicated ONT-LRS diagnostic assay within the NHS. Methods Patients undergoing brain tumour surgery were prospectively consented for surplus tissue sampling for research. LRS was performed on 54 fresh tissue and 78 fresh frozen tissue specimens. University of Birmingham scientists trained NHS staff to extract tumour DNA for sequencing using ONT PromethION flow cells. Research tools ROBIN, EPINN and MethyLYZR were adopted for real-time and batch methylome array. Results 132 specimens from 112 patients were analysed: mean age was 53(16.8); 70(63%) were male; self-reported ethnicity was White(76.5%), Asian(16.2%), Black(2.7%) or other(4.5%). Integrated SoC confirmed Glioblastoma IDH-wild type(59.5%), Astrocytoma IDH-mutant(27%), Oligodendroglioma IDH-mutant, 1p19q-codeleted(12.6%). Diffuse hemispheric glioma(H3G34-mutant; 0.9%), Anaplastic Pleomorphic Xanthoastrocytoma(0.9%), Subependymal gliant cell astrocytoma(0.9%), Pilocytic astrocytoma(0.9%), Meningioma(0.9%), Metastasis (Melanoma, Oesophageal, Renal, 2.7%). Integrating LRS within the SoC neuropathology workflow demonstrated 100% feasibility with no failures in tissue handling, DNA extraction, or sequencing. Amongst prospectively recruited patients(n = 54), NHS SoC integrated diagnosis was reported a median (IQR) of 23(18,32) days after surgery, whilst ROBIN obtained a methylome-based diagnosis within 1.4 days from surgery. In the total population (n = 132), LRS methylome-based diagnostic concordance was 77.6% for EPINN, 75.2% ROBIN and 56% MethyLYZR. Discordant samples included: tumours outside classifier remit(n = 3) and low tumour purity cases(n = 5). Conclusion This demonstrates good concordance between SoC and DNA LRS results. Building on close working partnership between surgeons, pathologists and scientists, we need access to larger, diverse sample populations to refine classifiers and understand their limitations.